2015
DOI: 10.1002/app.43235
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized electrospun polyacrylonitrile nanofibers as highly sensitive sensors in structural health monitoring of composite structures

Abstract: Electrospun polyacrylonitrile (PAN) nanofibers were stabilized at 2808C for 1 h in an ambient condition, and then carbonized at 8508C in inert argon gas for additional 1 h in order to fabricate highly pure carbonous nanofibers for the development of highly sensitive sensors in structural health monitoring (SHM) of composite aircraft and wind turbines. This study manifests the real-time strain response of the carbonized PAN nanofibers under various tensile loadings. The prepared carbon nanofibers were placed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Herein, Heck reaction was used to evaluate the catalytic performance of Pd@Carbon nanofibers. The optimized reaction condition was first adopted from our previous report 29 . As shown in Figure 8, the catalytic activity decreased in the order of Pd@Carbon‐800 > Pd@Carbon‐600 > Pd@Carbon‐400.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, Heck reaction was used to evaluate the catalytic performance of Pd@Carbon nanofibers. The optimized reaction condition was first adopted from our previous report 29 . As shown in Figure 8, the catalytic activity decreased in the order of Pd@Carbon‐800 > Pd@Carbon‐600 > Pd@Carbon‐400.…”
Section: Resultsmentioning
confidence: 99%
“…The optimized reaction condition was first adopted from our previous report. 29 As shown in Figure 8, the catalytic activity decreased in the order of Pd@Carbon-800 > Pd@Carbon-600 > Pd@Carbon-400. Pore size analysis and PALS result have demonstrated that the mesopores and defect holes inside carbon nanofibers were enlarged at high carbonization temperature.…”
Section: Heck Reactionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, electrospinning procedure has been used to produce polymer nanofibers embedded with additives such as anti-bacterial materials for water treatment and separation. Nanofibers have been gaining considerable attention due to their unique properties [43][44][45][46]. They are generally referred to as ultra fine fibers, possess some unique features, such as nanoscaled dimension in the cross-sectional area and macroscopic length on the axis of fibers.…”
Section: Synthesis Of Pan/pvp Nanofibersmentioning
confidence: 99%
“…They are generally referred to as ultra fine fibers, possess some unique features, such as nanoscaled dimension in the cross-sectional area and macroscopic length on the axis of fibers. There fibers possess high surface area, flexibility and porous structure which allow much higher sites for separation processes [43][44][45][46].…”
Section: Synthesis Of Pan/pvp Nanofibersmentioning
confidence: 99%